Riesgos y salud laboral de los trabajadores del hospital pablo Arturo Suarez de la ciudad de quito, propuesta de un sistema de control de riesgos biológicos. - Pacheco Estrada, Luis Eduardo (2013)
The staff that works providing its health services is exposed to all kinds of risk including physical, mechanical, chemical, ergonomic, psychosocial, and by the nature of their work. The biological risk overcomes. The biological risk consists of the presence of an organism, or substance of biological origin, which sets out vulnerability to human health, the problems caused by these factors are derived from the handling or exposure to pathogenic agents, such as body fluids, including blood, urine, feces, and other fluids, besides liquids and elements that have been in contact with contaminated patients and materials. The commonly biological factors found in the hospital environments are viruses, bacteria, fungi, and parasites. Viruses are very small organisms, which are developed within the living cells and when they are in, they control all the processes that take place within it. They reproduce quickly by seizing the enzymes and the biosynthetic machinery of their hosts and destroy the cell, which are very harmful to the body. Likewise, they perform as antigens that stimulate the cell to form antibodies that fight infection, by doing this; they lose the body's immune response. The virus travels through fluids such as blood, saliva, semen or urine of infected people and they are transmitted to other ones and presented in the environment. They caused many diseases such as influenza, mumps, measles, rabies, polio and others; they can be prevented with vaccines. However, there are other diseases that are very hazardous, and difficult to control, and some of them can be lethal, such as hepatitis B, HIV/AIDS, Influenza H1N1 or pneumonia, tuberculosis, some sexually transmitted diseases and respiratory infections among others. The bacteria also permeate through an infected scratch or cut, or by air. The fungi, is reproduced in moist places such as the mouth and intestines or in sweat body parts such as the head, feet, groin and in all the folds of the skin of the sexual organs. They are reproduced by lack of personal hygiene or because people have their defenses and produce very low diseases such as ringworm, athlete's foot, candidiasis, erysipelas or impetigo among others. The parasites are very dangerous organisms because they live from the others, in other words as a hosts. Nurses, doctors, technologists of laboratories are the most affected, in a lesser degree the staff cleaning, laundry, students, visitors, the administrative staff and patients.Hence the need for the performance of this research at Hospital Pablo Arturo Suarez, in Quito. This work was done based in bibliographic and field research to learn about the risks to which the workers in this House of Health and to establish appropriate mechanisms of control in order to maintain protected to their workers, patients, visitors and keep a friendly environment for them.